2020
DOI: 10.4103/jfmpc.jfmpc_1099_20
|View full text |Cite
|
Sign up to set email alerts
|

The level of the stigma of medical students at King Saud bin Abdulaziz University for Health Sciences, towards mentally ill patients

Abstract: Aim: The study aimed to measure the level of the stigma of medical students at King Saud bin Abdulaziz University for Health Sciences (KSAU-HS), Riyadh campus, towards mentally ill patients. Material and Methods: A cross-sectional survey was conducted in King Saud bin Abdulaziz University for Health Sciences (KSAU-HS), Riyadh. The data collection was started in July 2017 till March 2018. The students completed a self-administered questionnaire consisting of sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
(17 reference statements)
2
4
1
Order By: Relevance
“…Furthermore, our results indicated that having been diagnosed with mental illness or having a relative with mental illness was associated with lower levels of stigma. Our results concerning having a mental illness are consistent with those of the study by Alaqeel et al (2020) and of Kluemper et al (2021), and our results concerning having a relative with mental illness are also consistent with the findings of Alaqeel et al (2020).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, our results indicated that having been diagnosed with mental illness or having a relative with mental illness was associated with lower levels of stigma. Our results concerning having a mental illness are consistent with those of the study by Alaqeel et al (2020) and of Kluemper et al (2021), and our results concerning having a relative with mental illness are also consistent with the findings of Alaqeel et al (2020).…”
Section: Discussionsupporting
confidence: 92%
“…Comparing the pre and post psychiatry course groups, our results revealed no significant difference in stigma levels before and after the psychiatry course. Our results were consistent with those of the study conducted with students at the King Saud bin Abdulaziz University for Health Sciences using the CAMI scale (Alaqeel et al, 2020), the study by Muga and Hagali (2006), the study by Poreddi et al (2015), and an Egyptian study assessing the attitudes toward people with mental illness (Alaa El-Din et al, 2016), all of which demonstrated no mentionable difference in the attitudes before and after undergoing a course. The results of our study, however, are inconsistent with those of the study in South African students using the AMIQ scale (De Witt et al, 2019), Sulaiman Al Rajhi's students using the CAMI scale (Zitoun et al, 2021), and the mental illness perception study on Iranian medical students (Amini et al, 2013), all of which indicated an improvement in participants' stigma perception after exposure to psychiatry academic education.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The CAMI III questionnaire is widely used in countries around the world (Angermeyer et al, 2003; Högberg et al, 2008; Jee et al, 2006) and among different populations: the general population (Ewalds-Kvist et al, 2013; Ingram et al, 2019; Letovancová et al, 2017; Mehta et al, 2009; Winkler et al, 2016) and different segments of the population, such as medical professionals (nurses, physicians, psychiatrist, etc.) (Al-Awadhi et al, 2017; Sathyanath et al, 2016; Sévigny et al, 1999; Winkler et al, 2016), medical students (Alaqeel el al., 2020; Telles-Correia, 2015; Tong et al, 2020), cultural groups within a given society (Papadopoulos et al, 2013), or populations of particular cities or neighborhoods/areas in the cities (Brockington et al, 1993; Taylor & Dear, 1981; Taylor et al, 1979; Wolff et al, 1996).…”
Section: Introductionmentioning
confidence: 99%